Assessment of Valvular Dysfunction and Aortopathy Involvement in Patients with Bicuspid Aortic Valve: Echocardiographic Study - SERBOUT, Saousan; MAAROUFI, Anass; ZAHIDI, Hatim; Habbal, Rachida (Cardiology and Cardiovascular Medicine, 2020)
Bicuspid aortic valve is relatively common congenital cardiac anomaly, it is found in approximately 0,5-2% of the general population, which 75% of them are male. Was first described by vinci leonard and is defined by the presence of two abnormal leaflets, usually unequal in size, and not three aortic normal leaflets (as in the normal tricuspid valve). A prospective single center study had been performed in the department of Cardiology,Ibn rushd university hospital, to assess the evolution of valvular and aortic diameter in adults patients with bicuspid aortic valve. A total of 106 patients with bicuspid aortic valve were included during a follow up of 10 years. Aortic dimensions and other echocardiographic parameters were obtained from the echocardiography database of department. Patients with bicuspid aortic valve were mainly male (76,4%), with a mean age of 49 +/- 15 years and a significant proportion of hypertensive patients (50.9%). We notice a majoration of the number of patients with aortic stenosis over time (p < 0,001), with an involvement of transthoracic echocardiography parameters of aortic stenosis, a decrease of the aortic valve area, indexed or not, an increase of peak velocity and mean gradien, this progression was significantly higher (p = 0.0025) in subjects with aortic stenosis at inclusion:16cm/s/year against 4.6cm/s/y and an mean gradient of 3.5mmHg/year against 0.6mmHg/y. Whereas the progression of dilatation of sinus of Valsalva and tubular ascending aorta,was also more important in patients with aortic stenosis at inclusion compared with those who had not, aortic diameters between the 1st and the last control, sinus of valsalva: 0,17- 0,3 mm/year, tubular ascending aorta : 0,32 - 0,6 mm/year. A significant progression of aortic dimeter was obreserved in patients with a small aorta at inclusion compared of others. This study reinforces the fact that clinical and echographic surveillance of these patients, even i